Cyclization of sulfide, ether or tertiary amine-tethered N-sulfonyl-1, 2, 3-triazoles: a facile synthetic protocol for 3-substituted isoquinolines or dihydroisoquinolines. Issue 95 (7th October 2015) - Jiang, Yu; Sun, Run; Wang, Qiang; Tang, Xiang-Ying; Shi, Min
Abstract : A novel cyclization reaction of sulfide, ether or tertiary amine-tethered N -sulfonyl-1, 2, 3-triazoles, has been developed, efficiently affording 3-substituted isoquinoline or dihydroisoquinoline derivatives. Abstract : A facile synthetic method to access 3-substituted isoquinoline or dihydroisoquinoline derivatives has been developed via a novel cyclization reaction of N -sulfonyl-1, 2, 3-triazole derivatives by thermally induced rearrangement.